Participants’ Perceptions of using Computer Mediated Communication (CMC) as Part of a Distance Master’s Programme in Educational Technology and English Language Teaching - Teague, Joanna (Proceedings of the International Conference on Networked Learning, 2000)
Throughout 1999 a cohort of English language teachers participated in both collaborative and independent learning activities as part of a fully distance part-time Master’s programme in Educational Technology and English Language Teaching. The Master’s programme was run by The University of Manchester and the participants were located in different European countries and in Mexico. The distance students and tutors used both real-time (i.e. MOO, IRC, Conferencing) and asynchronous (e.g. email) telecommunications tools to communicate with each other. Research in this area (Bates 1995, Hiltz 1995, Naidu 1997, Hall 1997, Kay 1989, Harasim 1989, 1995, Nipper 1989, Paulsen 1998) suggests that given worthwhile reasons to participate in collaborative on-line tasks, adult distance learners can benefit from a Constructivist approach to education as they use CmC with their peers and tutors to negotiate, present, discuss and further clarify and develop their understanding of ideas and skills introduced in their distance course. This poster reports the findings from qualitative research into the distance students’ and the principle distance tutor’s perceptions of the use of synchronous and asynchronous CmC as part of a Master’s programme.